Parish Clergy of Central Chernozem Governorates of Russia in the Second Half of the 19th - early 20th Centuries: Assessment of Living Standards - S. A. Ikonnikov (Научный диалог)
The article is devoted to the study of material situation of the parish clergy of the Orthodox Russian Church in the second half of 19th - early 20th centuries. On the basis of archival documents and published sources, the standard of living of the clergy is analyzed, the total income of clerics is identified, taking into account the profits from all available sources of supply. Special attention is paid to the analysis of property inequality of spiritual persons. The author comes to a conclusion that in the period under review, the income of the clergy of the Central Chernozem dioceses has increased significantly due to the growth of the congregation and the increase in ritual load, as well as to government measures taken in the framework of implementation of the ways of financial support of clergy developed by the Office in the Affairs of the Orthodox clergy. It is noted that, despite the significant increase in revenues, a set of problems related to material support of parishes finally was not solved. According to the author, this is the reason for the growth of protest moods within the spiritual class in the early 20th century.